IDEALISM, PRAGMATISM, OPPORTUNISM: Explaining Islamist Movements in Contemporary Indonesia - Permata, Ahmad Norma (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Since democratization, Islamists in Indonesia have had a surprisingly significant influence. While scholars once believed that Islamist movements were marginal and losing influence, the mass mobilizations of December 2016 and Islamists’ centrality to the 2019 Presidential election has forced scholars to reconsider the power and place of Islamism in Indonesia. However, existing studies seemed constrained by the uncritical assumption of Islamism as an ideology directly influencing behaviors. This article suggests that one way to move the literature forward is to take Islamism as a mental model, which helps to distinguish it from Islam as a religion clinically and to understand the structure of Islamist behaviors better. This article finds three patterns of behavior among contemporary Islamist movements, i.e., vigilante idealism of FPI, multivocal pragmatism of PKS, and complacence opportunism of PBB, which are better explained by differences in their mental models rather than their religious interpretations or their commitments to Islamist agenda